Analysis of Energy Consumption and Carbon Emissions in Indonesia - Bayu Rahmadi Putra; Sulistya Rusgianto (Jurnal Ekonomi Pembangunan, 2023)
The development process that uses excessive fossil energy in industrial activities impacts increasing carbon emissions in Indonesia. The purpose of this study is to determine how the relationship between energy consumption (EN), economic growth (GDP), carbon emissions (CO2), and human development (HDI) in Indonesia in the Maqashid Syariah review. Using the Vector Error Correction Model (VECM) approach, it is found that in the long run, carbon emissions negatively affect energy consumption. Meanwhile, economic growth and human development positively affect energy consumption. Energy consumption and economic growth positively affect human development in the short term. Meanwhile, carbon emissions hurt HDI, while HDI has a positive effect on carbon emissions. Meanwhile, the Granger causality test results show that HDI has a unidirectional causality relationship with Indonesia's energy consumption, economic growth, and carbon emissions. This result indicates that energy consumption in Indonesia has not provided protection and benefits for the community by Maqashid Sharia, which prioritizes the principle of sustainable development